Zeroing in: achieving zero complications in lumbar puncture – a quality improvement initiative to reduce complications at the University Hospital of North Norway - Susanne Gaarden Ingebrigtsen; Agnethe Eltoft; Thomas Karsten Kilvaer (BMJ Open Quality)
Background Lumbar puncture (LP) is an essential diagnostic procedure in neurology, but carries risk, with post-lumbar puncture headache being the most frequent complication. In 2017, a severe complication with intracranial haemorrhage following LP in Northern Norway led to an evaluation of LP procedures and resulted in the development of a new unified regional procedure.Local problem At the University Hospital of North Norway (UNN), 10% of LPs performed in 2017 resulted in a complication. A survey identified gaps in protocol adherence, physician training, and patient education.Intervention Aiming to reduce LP complication rates from 10% to 1% by January 2019, we implemented standardised protocols, introduced smaller gauge needles, enhanced physician training and improved patient education.Results Complication rates dropped to 1%, achieving 107 consecutive complication-free procedures by January 2019, with sustained improvement over subsequent years.Conclusion Standardised protocols, physician training, introduction of smaller gauge needles and patient education significantly reduced LP complications. Educating patients on expectations and post-procedure care was critical in preventing unnecessary admissions and outpatient visits.